2019
DOI: 10.1002/ceat.201800475
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Solute Properties and Water Matrix on Nanofiltration of Pesticides

Abstract: The application of different nanofiltration membranes for the separation of pesticides, i.e., atrazine and dimethoate, from aqueous solutions is described. The nanoflitration membranes DK, NF270, NF200, and NF90 were tested for the pesticide retention performance in a stirred dead-end filtration system. NF90 demonstrated the best pesticide retention with over 95 % for atrazine and approximately 80 % for dimethoate. All membranes consistently showed better retention of atrazine than of dimethoate. Dissolving th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Similar trend was observed in another study by Tan et al [32] in which river water with the most ions displayed the highest retention and lowest permeate flux of atrazine and dimethoate pesticides using DK, NF270, NF200 and NF90 membranes. For instance, the retention and permeate flux of atrazine in deionised water 50% and 2.1×10 -5 m 3 /m 2 •s, respectively.…”
Section: Feed Solution Ionic Chargesupporting
confidence: 90%
See 2 more Smart Citations
“…Similar trend was observed in another study by Tan et al [32] in which river water with the most ions displayed the highest retention and lowest permeate flux of atrazine and dimethoate pesticides using DK, NF270, NF200 and NF90 membranes. For instance, the retention and permeate flux of atrazine in deionised water 50% and 2.1×10 -5 m 3 /m 2 •s, respectively.…”
Section: Feed Solution Ionic Chargesupporting
confidence: 90%
“…Like positively charged molecules, micropollutants with larger dipole moment could adsorb onto the charged membrane surface, making it possible for them to diffuse through the membrane. Hence, there was a lower retention of large dipole moment solutes [31,32].…”
Section: Pesticides Ionic Chargementioning
confidence: 99%
See 1 more Smart Citation
“…These membranes are usually targeted towards softening of water, being partially effective in removing dissolved ions [19]. Previous studies have reported pesticide removal e ciencies ranging from 30.00% to greater than 90.00% for phenylurea, phenoxyacetic acid, triazines, dithiolane pesticides organophosphate or synthetic auxin classes [20][21][22][23][24]. Meanwhile, reverse osmosis membranes have a molecular cut-off smaller than 100 Da [25] and are the standard on desalination processes.…”
Section: Introductionmentioning
confidence: 99%